Autism and Learning Disabilities: A relational-intersectional perspective - Urbistondo Cano, Fran (Murmurations: Journal of Transformative Systemic Practice, 2022)
In this article, I develop a relational-intersectional perspective in my work with autistics with learning disabilities and their paid care staff in social care in England. I propose and illustrate a shift from normalisation to depathologisation in autism as it has already occurred with “homosexuality” classified as a mental disorder in the 70s. I also explore the performativity of “being LGBTQ+” and “being autistic” in a neurotypical-heteronormative-ableist-led society. I point out a possible confluence of intersectionality and the social graces model. I also dig into what research tells us about the lives of people with learning disabilities and autism and the lives of care workers in social care. Finally, I emphasise the benefits of working from a relational-intersectional perspective in a relational approach that has social justice at the heart of its values.